CORPORATE SOCIAL RESPONSIBILITY BASED OF SHARIA AGROPENEURS FOR WOMEN’S EMPOWERMENT AND CHILD-FRIENDLY - Khulsum, Umi; Zais, Ferliansyah; Risna, Meilia; Utami, Pertiwi (Universitas Muhammadiyah Bengkulu, 2025)
The research conducted aims to investigate the practice of corporate social responsibility (CSR) based on sharia agropreneurs for women and child-friendly. The location of the research is at PT. Tanah Harapan Wisata Alam (Hopeland Camp), Bogor. The research method used is a qualitative method with data collection through observation, interviews, and literature studies related to agropreneurs, sharia principles in business, and CSR practices. The findings reveal that the CSR model based on sharia agropreneurship can provide positive and beneficial impacts from the social and industrial aspects of agropreneurship. The principles of Islamic business carried out in this model are expected to have implications for women's empowerment and child-friendly. So that they can think creatively, and imaginatively, and can see business opportunities that are by Islamic teachings. They are also expected to be able to answer the challenges of the future of agriculture through the model developed